Spanish Validation of the Child Pornography Offender Risk Tool. (August 2021) - Soldino, Virginia; Carbonell-Vayá, Enrique J.; Seigfried-Spellar, Kathryn C.
The current study examined the validity of the Child Pornography Offender Risk Tool (CPORT) in a sample of 304 men arrested in Spain for child pornography (CP) offenses, distinguishing between CP-exclusive offenders ( n = 255) and CP offenders with other criminal involvement ( n = 49). In our 5-year fixed follow-up analysis, we observed a 2.3% sexual recidivism rate for the whole sample (2.0% new CP offenses, 0.3% new contact sexual offenses). Receiver operating characteristic (ROC) analyses detected some relative predictive ability of the CPORT for CP recidivism outcomes when the Correlates of Admission of Sexual Interest in Children (CASIC) was used to replace missing CPORT Item 5. Specifically, both CPORT and CASIC total scores might help predict new CP offending among CP-exclusive offenders (area under the curve [AUC] = .57 and .70, respectively). Calibration analyses found that the observed recidivism rates were much lower than the expected recidivism rates presented by the tool developers, and, thus, suggest caution over the use of these norms for applied risk assessment. Our findings provide, to some extent, preliminary evidence of CPORT cross-cultural validity.